Contribution of screening and survival differences to racial disparities in colorectal cancer rates - Lansdorp_Vogelaar, Iris; Kuntz, K.; Knudsen, A.; Van Ballegooijen, M.; Zauber, A.; Jemal, A. (American Association for Cancer Research Inc, 2012)
Background: Considerable disparities exist in colorectal cancer (CRC) incidence and mortality rates between blacks and whites in the United States. We estimated how much of these disparities could be explained by differences in CRC screening and stage-specific relative CRC survival. Methods: We used the MISCAN-Colon microsimulation model to estimate CRC incidence and mortality rates in blacks, aged 50 years and older, from 1975 to 2007 assuming they had: (i) the same trends in screening rates as whites instead of observed screening rates (incidence and mortality); (ii) the same trends in stage-specific relative CRC survival rates as whites instead of observed (mortality only); and (iii) a combination of both. The racial disparities inCRC incidence and mortality rates attributable to differences in screening and/or stage-specific relative CRC survival were then calculated by comparing rates from these scenarios to the observed black rates. Results: Differences in screening accounted for 42% of disparity in CRC incidence and 19% of disparity in CRC mortality between blacks and whites. Thirty-six percent of the disparity in CRC mortality could be attributed to differences in stage-specific relative CRC survival. Together screening and survival explained a little more than 50% of the disparity in CRC mortality between blacks and whites. Conclusion: Differences in screening and relative CRC survival are responsible for a considerable proportion of the observed disparities in CRC incidence and mortality rates between blacks and whites. Impact: Enabling blacks to achieve equal access to care as whites could substantially reduce the racial disparities in CRC burden.